Effect of Probiotic Oral Suspension on Disease Severity in Chronic Obstructive Pulmonary Disease Patients-A Randomized Control Trial - Muhammad Younus, Kamal Din, Sohail Anwar, Yasir Nasir (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Probiotics has been broadly used in the healing of respiratory illness, but their efficacy for treating chronic obstructive pulmonary disease (COPD) has not been well studied. Objective: To determine the effects of probiotic oral suspensions on disease severity in COPD patients assessed by Rate of exacerbation, COPD assessment Test (CAT) Score and C - reactive protein (CRP). Material and Method: This Randomized controlled study was conducted at Institute of TB and Chest medicine (indoor and outdoor both), Mayo Hospital Lahore. Duration of study was one year, September 2020 to August 2021.Total 80 patients fulfilling the inclusion criteria are taken from the chest medical ward, Mayo Hospital Lahore. Their basic demographic information was recorded. Recruitment and randomization of patients was done. Cases were given Probiotic ampule (Enterogermina sachets containing Bacillus Clausii) 2 billion daily for 6 months and controls were given placebo. Patients were followed on monthly basis and they were assessed Rate of exacerbation, COPD assessment test (CAT) Score and CRP. Data was entered by SPSS-26. Quantitative variables like age was represented as mean + a SD. Qualitative variable like gender was represented as frequency and percentage. Comparison of two groups Placebo and probiotic group was carried out by independent sample t-test. p-value <0.05 taken as significant. Results: Mean age of patients in treatment along with in placebo assembly was 48.27±11.67 and 49.32±10.30 years. Number of exacerbations was compared in both groups till 6 months. At 1st month post treatment significant difference was seen in number of exacerbations (No exacerbations: Treatment: 73% vs. Placebo: 45%, p-value=0.023) and from 2nd month till 6th month no significant difference was seen for exacerbations in both groups. For CRP level no significant difference was seen in treatment and placebo before and after treatment. i.e. After Treatment (Treatment: 18.81 vs. Placebo: 19.888, p-value=0.874). For FEV1 no significant difference was seen in treatment and placebo before and after treatment. i.e. After Treatment (Treatment: 1.55 vs. Placebo: 1.57, p-value=0.876). Mean CAT score after treatment showed significant difference for treatment and placebo groups. i.e. (Treatment: 15.17 vs, Placebo: 18.42, p-value=0.021). CAT score was significant higher in placebo group. Conclusion: Results of this study demonstrate that addition of oral suspensions of probiotic had a significant impact on rate of exacerbation and CAT score in contrast to placebo group. However, no significant difference was seen for CRP levels after treatment in both groups. Keywords: COPD, Probiotic, CAT score, CRP, Rate of exacerbation